Are microloans bad for growth? - Patrick M. Emerson; Bruce McGough (Institute for the Study of Labor (IZA), 2010)
This paper constructs a two-period overlapping generations model of human capital investment decisions where a microloan program designed to finance entrepreneurial activities is active. It is shown that, in the presence of human capital externalities (social returns to education) there exists a range of microloan amounts that are growth depressing and welfare decreasing through their affect on the opportunity cost of schooling. By increasing the opportunity cost of schooling, microloans divert investment away from human capital: by failing to internalize the social returns to education, households' individually optimal investment decisions in the face of microcredit availability act to depress the growth of the economy and result in sub-optimal welfare outcomes.
Keywords: E24; O10; O40; 330; microloans; growth; human capital